HISTOLOGICAL STUCTURE OF THE DOG’S SKIN WITH DERMATITIS IN EXTREMITAS CAUDAL, DORSUM, AND ABDOMEN - Putra, Putu Dian Purnama; Suwiti, Ni Ketut; Susari, Ni Nyoman Werdi (Buletin Veteriner Udayana; Vol. 14 No. 3 June 2022DO - 10.24843/bulvet.2022.v14.i03.p15, 2022)
Skin is the largest organ in dogs that serves to overcome the presence of foreign agents both from exogenous and endogenous. One of the health problems on dog skin is dermatitis and can be found in almost all parts of the body. This study aims to observe changes in the histological structure of the skin of male and female dogs suffering from dermatitis on the caudal, dorsum, and abdominal extremities. A total of 24 research samples in the form of skin organs were collected from patients at the Udayana University Animal Hospital Teaching. The results showed that there was no difference (P>0.05), the histological structure of the skin of male and female dogs suffering from dermatitis, both skin from the caudal extremities, dorsum and abdomen. Histological changes found were: parasitic segments, hiperkeratosis, necrosis, degeneration, edema, hyperplasia, infiltration of stratum reticular fat cells, and infiltration of inflammatory cells. Infiltration of inflammatory cells, neutrofils, and macrophages are mostly found in the dermis while basofils are found in the epidermis.